2017
DOI: 10.1111/cen.13358
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in obese girls with polycystic ovarian syndrome is associated with a decrease in Anti‐Muellerian Hormone concentrations

Abstract: AMH was increased in adolescent girls with PCOS and normalized with weight loss. AMH was cross-sectionally and longitudinally related to hyperandrogenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Median, Adolescence: Lee, Lashen, Anderson, Pinola, Elchuri, Cui, Hart, Hernandez and Yetim . Mean, Adolescence: Lee, Elchuri, Cui, Akin, Kim, Reinehr and Sophor…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Median, Adolescence: Lee, Lashen, Anderson, Pinola, Elchuri, Cui, Hart, Hernandez and Yetim . Mean, Adolescence: Lee, Elchuri, Cui, Akin, Kim, Reinehr and Sophor…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five studies reported serum AMH levels between 10 and 18 years Only five studies reported serum inhibin levels, and only three reported AFC in adolescence . Following a transient decrease at puberty as detailed above, a broad consensus across studies show constant levels of serum AMH during adolescence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations